Education versus indoctrination: Contextualising the crisis in higher education in South Africa - Petrus, T. (South African Journal of Higher Education, 2019)
Since the emergence of the national protests at Higher Education Institutions (HEIs) in South Africa in 2015, both the public media and social media platforms were inundated with debates justifying the credibility and validity of the protests. It appears that the public and social media had succeeded in swaying public opinion in favour of the protests, as much media attention was focused on portraying the protests in the same manner as those of June 1976, namely that these were students fighting for equality in education, similar to those of 1976. However, since the protests hit their peak in 2015, and even through 2016, what have we learnt about the crisis in higher education that the protests have created? First, is there a crisis? Second, do the protests reflect the reality of the state of education in South Africa, namely, that institutions no longer seek to educate, but to indoctrinate? These are the key questions addressed in this article.